2020
DOI: 10.1186/s13195-020-00644-z
|View full text |Cite
|
Sign up to set email alerts
|

The short-term effects of sedentary behaviour on cerebral hemodynamics and cognitive performance in older adults: a cross-over design on the potential impact of mental and/or physical activity

Abstract: Background Sedentary behaviour might be a potential risk factor for cognitive decline. However, the short-term effects of sedentary behaviour on (cerebro) vascular and cognitive performance in older people are unknown. Methods We used a cross-over design with 22 older adults (78 years, 9 females) to assess the short-term hemodynamic and cognitive effects of three hours uninterrupted sitting and explored if these effects can be counteracted with regular (every 30 min) two-minute walking breaks. In addition, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…We did not expect effects on other domains. Although some previous studies show an acute effect of PA breaks on cognitive outcomes [9,10], a majority, including our work, shows that PA breaks do not acutely improve cognitive performance [8,14,40,41]. Since these previous studies used different meal compositions, our study adds the important novel observation that meal composition does likely not explain between-study differences in outcomes.…”
Section: Cognition and Perceivable Benefitsmentioning
confidence: 58%
See 1 more Smart Citation
“…We did not expect effects on other domains. Although some previous studies show an acute effect of PA breaks on cognitive outcomes [9,10], a majority, including our work, shows that PA breaks do not acutely improve cognitive performance [8,14,40,41]. Since these previous studies used different meal compositions, our study adds the important novel observation that meal composition does likely not explain between-study differences in outcomes.…”
Section: Cognition and Perceivable Benefitsmentioning
confidence: 58%
“…This test battery is sensitive and has been validated for use in biomedical research [39]. It has moreover been previously used in a study investigating the effects of breaking up sitting on cognitive function [40]. The investigated cognitive domains have been assessed in previous research on PA breaks [8e10, 14,40,41] and also meal composition [35,42].…”
Section: Cognitive Performancementioning
confidence: 99%
“… Zlatar et al (2019) confirmed that longer sedentary time was significantly associated with lower CBF in lateral and medial frontal regions, which confirmed the earlier work by Bailey et al (2013) showing that sedentary aging is associated with a longitudinal decline in CBF. Finally, the literature has persistently confirmed the positive impact of regular physical activity on CBF ( Kleinloog et al, 2019 ; Hartman et al, 2020 ; Maasakkers et al, 2020 ; Steventon et al, 2020 ).…”
Section: Sedentary Lifestylementioning
confidence: 86%
“…The study found a significant decline of cerebral flow velocity in uninterrupted sitting (− 3.2 ± 1.2 cm/s) compared to 2-min walk breaks (0.6 ± 1.5 cm/s) but not 8-min walk breaks (− 1.2 ± 1.0 cm/s). In contrary to earlier studies, Maasakkers et al (2020) failed to find a significant difference in cerebral flow velocity or cerebral vasomotor functions between uninterrupted (3 h) and interrupted sitting bouts (2 min walk break every 30 min for 3 h) combined with or without mental tasks in 22 elderly adults (78 years) [ 63 ]. The aforementioned inconsistent findings regarding the effects of interrupted sitting bouts on the cerebral flow velocity and perfusion makes it difficult to extrapolate the effects of such interventions on cognitive functions.…”
Section: Methodsmentioning
confidence: 91%
“…It could be hypothesized that breaking up sitting bouts may improve postprandial glucose metabolism, insulin resistance, lipid profile and other cardiometabolic risk biomarkers such as inflammatory markers. Though the reduction in cardiometabolic risk factors associated with the breaking sedentary behavior is perceived to regulate endothelial integrity, cortical perfusion and thus may improve cognitive functions [ 21 ], early experimental mechanistic studies failed to establish the relation between cardiometabolic risk factors, endothelial functions and cognitive functions [ 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%